2003
DOI: 10.1074/jbc.m210427200
|View full text |Cite
|
Sign up to set email alerts
|

mSharp-1/DEC2, a Basic Helix-Loop-Helix Protein Functions as a Transcriptional Repressor of E Box Activity and Stra13 Expression

Abstract: Transcription factors belonging to the basic helixloop-helix (bHLH) family play critical roles in the regulation of cellular differentiation of distinct cell types. In this study, we have characterized the DNA-binding and transcriptional properties of the bHLH factor mSharp-1/DEC2. mSharp-1 belongs to the Hairy/Enhancer of Split subfamily of bHLH factors and exhibits the highest structural and sequence identity with Stra13. We show that mSharp-1 specifically binds to the E box motif (CANNTG) as a homodimer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
104
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 53 publications
7
104
0
Order By: Relevance
“…8C). Furthermore, we examined the expression of DEC2, a homolog of DEC1/Stra13 that can suppress the transcription activity of myoD protein (2). As shown by RT-PCR, the expression of DEC2 does not change significantly in C2C12 cells up to 3 days at 0.5 or 0.01% O 2 (Fig.…”
Section: Myogenesis Under Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…8C). Furthermore, we examined the expression of DEC2, a homolog of DEC1/Stra13 that can suppress the transcription activity of myoD protein (2). As shown by RT-PCR, the expression of DEC2 does not change significantly in C2C12 cells up to 3 days at 0.5 or 0.01% O 2 (Fig.…”
Section: Myogenesis Under Hypoxiamentioning
confidence: 99%
“…2 , 0.1 mM EDTA, 0.5% NP-40, 1 mM dithiothreitol (DTT), 0.5 mM phenylmethylsulfonyl fluoride (PMSF), 320 mM sucrose]. After centrifugation, the cytoplasmic fractions were collected and stored at Ϫ80°C until use.…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we found a direct correlation between BHLHB3 and BHLHB2 transcript levels (Spearman's r ¼ 0.508; P ¼ 0.006), whereas (Li et al, 2003) described an inverse relationship between BHLHB3 and BHLHB2 expression. On the basis of a previous study indicating repression of mouse Bhlhb2 promoter activity by Bhlhb3 transfection in mouse fibroblast cell line 10T1/2 (Azmi et al, 2003), we tested the hypothesis that BHLHB3 directly affects mRNA levels of BHLHB2. Measurement of BHLHB2 mRNA levels in NCI-H520 lung cancer cells stably transfected to overexpress BHLHB3 (see Figure 1 legend for details of kinetic reverse transcriptase) revealed only a slight decrease (0.56±0.10-fold, mean±s.e., n ¼ 12) as compared to vector-transfected cells, arguing against any significant, if any, direct modulation of BHLHB2 expression by BHLHB3 and instead, suggesting that the observed correlation between BHLHB2 and BHLHB3 expression in the normal lung and lung ADCA tissues rests in common transcription regulation.…”
mentioning
confidence: 99%
“…Sharp-1, a basic helix-loop-helix transcription factor, is one of the transcriptional corepressors modulating C/EBPs and PPAR␥ activity. Sharp-1 binds to class B E-box sites with high affinity to repress the transcription of target genes and also associates with distinct corepressors, including HDAC1, SIRT1, and the histone methyltransferase G9a, to inhibit gene transcription (7). Taneja and co-workers (8) found that Sharp-1 interacts with and inhibits the transcriptional activity of both C/EBP␤ and C/EBP␣ by retaining HDAC1 and G9a at the C/EBP regulatory sites on the C/EBP␣ and PPAR␥2 promoters to inhibit their expression and, thus, adipogenesis, identifying Sharp-1 function as a negative regulator during adipogenesis.…”
mentioning
confidence: 99%